Assessment Of Orthodontıc Treatment Need And Severıty Of Malocclusıon In School Chıldren Aget 7 To 12 Years - Hülya Kılıçoğlu (Galenos Yayinevi, 2004)
The aim of this study was to evaluate the severity of malocclusion and to assess the need for orthodontic treatment among 7-12 years old schoolchildren (246 girls, 266 boys). No subject had any history of craniofacial abnormalities and none had undergone prior orthodontic therapy. The Treatment Priority Index (TPI) was used to record and measure the malocclusions. To assess the range of malocclusions the "Malocclusion Severity Estimate" (MSE) was also used. The findings were that 41.4% of the observed population showed normal occlusion, 39.6% had minor manifestation of malocclusion and treatment need was slight, 15.2% of the subjects showed definite malocclusion, 2.3% had severe malocclusion and 1.4% had a very severe handicap with a mandatory treatment requirement. The differences between the TPI values of the boys and girls were evaluated by chi-square, the TPI differences between ages were examined by using one way ANOVA. The differences between the TPI values of the boys and girls and the TPI differences between ages were not found statistically significant.